Just in time collision avoidance – A review. (May 2020) - Bonnal, Christophe; McKnight, Darren; Phipps, Claude; Dupont, Cédric; Missonnier, Sophie; Lequette, Laurent; Merle, Matthieu; Rommelaere, Simon
Abstract: The ever increasing number of orbital objects since 1957 raises numerous questions concerning future sustainability of space. Among the 34, 000 objects larger than 10 cm in orbit, 20, 000 only are cataloged. These cataloged objects include roughly 2000 active satellite, among which less than 1500 are maneuverable. All the rest are orbital debris, large satellites of launcher upper stages, mission related objects, inert pieces from fragmentations or collisions, with no maneuvering capabilities. Collision Avoidance is a common practice when at least one maneuvering satellite is involved, even though it requires a very significant effort to do so. But it is today not possible to avoid collisions among two debris, which represent by far the most frequent collision scenario. It appears necessary to find solutions to avoid such collisions as they have the potential to generate thousands of new orbital pieces and feed to so-called Kessler syndrome; indeed, numerous publications underline the frequent near-misses among very large derelict, and the consequences such collisions would have. Several solutions for such "Just in time Collision Avoidance (JCA)" have been proposed and are recalled in the paper. Three of them have recently been studied in order to assess their feasibility, and appear promising. The use of an orbital laser system can first drastically improve our the accuracy of the ephemerids, second impart a very small ΔV to a passive debris early enough to enable a significant increase in distance between the two objects. Another solution which appears very promising considers the launch on a small sounding rocket of a system releasing a cloud of particle and gas in front of one of the debris; the associated drag, even very small, is enough to lower the probability of an announced collision. Swarms of nano-tugs could also be attached to the most hazardous derelicts, de-tumble them, and slightly modify their trajectory in order to prevent collisions. Highlights: Collision between two large non maneuverable objects is one of the key problems in orbit. Just-in-time Collision Avoidance JCA may help preventing such collisions. Small laser orbital stations may provide solutions to track and nudge the large debris. Insertion of a suborbital cloud of particles in front of a debris may prevent a collision. Nanotugs, attached to a large debris, may control it and prevent a collision.